The impact of cryopreserved sperm on intrauterine insemination outcomes: is frozen as good as fresh? - Cherouveim, Panagiotis; Vagios, Stylianos; Hammer, Karissa; Fitz, Victoria; Jiang, Victoria S.; Dimitriadis, Irene; Sacha, Caitlin R.; James, Kaitlyn E.; Bormann, Charles L.; Souter, Irene (Frontiers in Reproductive Health, 2023)
Introduction: Frozen sperm utilization might negatively impact cycle outcomes in animals, implicating cryopreservation-induced sperm damage. However, in vitro fertilization (IVF) and intrauterine insemination (IUI) human studies are inconclusive. Methods: Retrospective review of 5,335 IUI(±OS) cycles from a large academic fertility center. Cycles were stratified based on utilization of frozen (FROZEN, n=1,871) instead of fresh-ejaculated sperm (FRESH, n=3,464). Main outcomes included HCG-positivity, clinical pregnancy (CP), spontaneous abortion (SAB) rates. Secondary outcome was livebirth (LB) rate. Odds ratios (OR) for all outcomes were calculated utilizing logistic regression and adjusted for maternal age, day-3 FSH, and OS regimen. Stratified analysis was performed based on OS subtype [gonadotropins, oral medications (OM): clomiphene citrate and letrozole, and unstimulated/natural]. Time-to-pregnancy and cumulative pregnancy rates were also calculated. Finally, three sub-analyses were performed: i) first cycle only, ii) partner’s sperm only, and iii) after excluding female factor infertility. Results: HCG-positivity and CP were lower in the FROZEN compared to the FRESH group (12.2% vs. 15.6%, p<0.001; 9.4% vs. 13.0%, p<0.001, respectively), which persisted only among OM cycles after stratification (9.9% vs. 14.2% HCG-positivity, p=0.030; 8.1% vs. 11.8% CP, p=0.041). Among all cycles, adjOR(95%CI) for HCG-positivity and CP were respectively: 0.75(0.56-1.02), and 0.77(0.57-1.03), ref: FRESH. In OM cycles, adjOR(95%CI) for HCG-positivity [0.55(0.30-0.99)] and CP [0.49(0.25-0.95), ref.: FRESH] favored the FRESH group but showed no differences among gonadotropin and natural cycles. SAB odds did not differ between groups among OM and natural cycles but were lower in the FROZEN among gonadotropin cycles [adjOR(95%CI): 0.13(0.02-0.98), ref.: FRESH]. There were no differences in CP and SAB when analysis was limited to first cycles, partner’s sperm, or after excluding female factor infertility. Nevertheless, time-to-conception was slightly longer in the FROZEN compared to the FRESH group (3.84 vs. 2.58 cycles, p<0.001). No significant differences were present in LB and cumulative pregnancy results, other than higher odds for LB [adjOR(95%CI): 1.08(1.05-1.12)] and higher cumulative pregnancy rate (34% vs. 15%, p=0.002) in the FROZEN group compared to FRESH among natural cycles. Conclusion: Overall, clinical outcomes did not differ significantly between frozen and fresh sperm IUI cycles, although specific subgroups might benefit from fresh sperm utilization.